Implementation of the Resilient Village at Gunung Geulis Village, Sukaraja Sub-regency, Bogor, West Java - Admiral Musa Julius; Nrangwesthi Widyaningrum; Ainun Najib; Andi Ahmad Aminullah; Hani Syarifah; Hendro Pratikno; Ifad Fadlurrahman; Khairunnisa Adri; Tego Suroso; Rizkia Mutiara Ramadhani; I Dewa Ketut Kerta Widana (Swabumi, 2020)
This study aims to analyze (1) the participation of the community of Gunung Geulis Village, particularly vulnerable groups, in managing resources in order to reduce disaster risk; (2) increasing the capacity of citizens and officials on disaster management and (3) the performance of the Village DRR forum. This study uses a qualitative method. The subjects of this study were Gunung Geulis village secretaries using the interview method. The results showed (1) personnel from the disaster management forum planted trees on landslides prone area and made archery embankments, (2) Gunung Geulis Village as a program implementer of Disaster Resilient Village had been actively conducting routine and ongoing training every once a month in an effort capacity development on disaster management, (3) the Disaster Risk Reduction (DRR) forum of Gunung Geulis village has carried out passive mitigation efforts such as making mapping and analysis of disaster risk, even though there is no document compiled. DRR personnel also carry out mitigation and early warning efforts through information through pamphlets, brochures, and other village meetings. In addition, active mitigation efforts have been made by the DRR team.